1999
DOI: 10.1128/mcb.19.2.1289
|View full text |Cite
|
Sign up to set email alerts
|

Protective Function of von Hippel-Lindau Protein against Impaired Protein Processing in Renal Carcinoma Cells

Abstract: The absence of functional von Hippel-Lindau (VHL) tumor suppressor gene leads to the development of neoplasias characteristic of VHL disease, including renal cell carcinoma (RCC). Here, we compared the sensitivity of RCC cells lacking VHL gene function with that of RCC cells expressing the wild-type VHL gene (wtVHL) after exposure to various stresses. While the response to most treatments was not affected by the VHL gene status, glucose deprivation was found to be much more cytotoxic for RCC cells lacking VHL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 57 publications
1
40
0
2
Order By: Relevance
“…Maxwell et al (1999) proposed a model in which VHL forms complexes with the HIF-a subunits under normal cellular O 2 tension, thereby targeting the HIF-a subunits for destruction. In addition, ubiquitination of cellular proteins in VHL de®cient cells was elevated after glucose deprivation supporting an involvement of VHL in ubiquitin dependent degradation of proteins (Gorospe et al, 1999). Recent ®ndings point to an involvement of the HIF-1 complex in tumor angiogenesis (Maxwell et al, 1997;Carmeliet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Maxwell et al (1999) proposed a model in which VHL forms complexes with the HIF-a subunits under normal cellular O 2 tension, thereby targeting the HIF-a subunits for destruction. In addition, ubiquitination of cellular proteins in VHL de®cient cells was elevated after glucose deprivation supporting an involvement of VHL in ubiquitin dependent degradation of proteins (Gorospe et al, 1999). Recent ®ndings point to an involvement of the HIF-1 complex in tumor angiogenesis (Maxwell et al, 1997;Carmeliet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that TRC8 may be somewhat analogous to the Hrd1/der3p protein complex in the ER, perhaps targeting a subset of proteins for degradation in a VHL-dependent manner. Interestingly, Gorospe et al (1999) reported that VHL mutant RCC cell lines were more sensitive to agents that a ect protein folding (and the unfolded protein response) than wild type VHL cells. Thus, TRC8 might conceivably be involved in this aspect of VHL function.…”
Section: Discussionmentioning
confidence: 99%
“…Each pair was composed of one cell line with null VHL status (parental) and one expressing wild-type VHL (wtVHL) (described in Gorospe et al, 1999). Cultures were exponentially growing, with a density at the time of collection of approximately 60 ± 70%.…”
Section: Construction and Analysis Of Sage Libraries From Rcc Cells Wmentioning
confidence: 99%
“…Matched pairs of the human RCC lines 786 ± 0, UMRC6 and UOK-121 were obtained that either expressed no functional VHL (parental) or expressed a wild-type VHL (wtVHL) allele through stable transfection; both 786 ± 0 parental and UOK-121 parental cells were transfected with corresponding empty vectors and selected accordingly, while UMRC6 parental cells did not carry an empty vector (Gorospe et al, 1999). All cells were cultured in Dulbecco's modi®ed essential medium (Gibco-BRL) supplemented with 10% fetal bovine serum.…”
Section: Cell Culture and Tnfa Cytotoxicity Assaymentioning
confidence: 99%